Modelos de calidad y gestión en educación superior, un análisis comparativo (2012)
This research contrasts two models of quality management: the institutional model of accreditation for institutions of higher education in Colombia and the ISO 9001 international model, using the Context, Input, Process, Product (CIPP) assessment model proposed by Stufflebeam. It pursues the search for characteristics that should have the quality assessment of institutions of higher education in order to ensure compliance of the purposes they pursue and thus contribute to the continuous improvement in the quality management of higher education.As a working methodology it consolidates information on the assessment and accreditation with regard to higher education in Colombia and the implementation of quality management systems in institutions of higher education, to obtain data from secondary sources to evaluate the categories and variables in relation to the CIPP model.It generates a correlation matrix product of the analysis of the requirements and factors reviewed from the perspective of each CIPP variable model and weighing the convergent, divergent and complementary aspects. This process highlighted some of the characteristics that should have the quality assessment in institutions of higher education in Colombia